Inflammation and vascular dysfunction: The negative synergistic combination of diabetes and COVID‐19. Issue 7 (22nd July 2022) - Bolla, Andrea Mario; Loretelli, Cristian; Montefusco, Laura; Finzi, Giovanna; Abdi, Reza; Ben Nasr, Moufida; Lunati, Maria Elena; Pastore, Ida; Bonventre, Joseph V.; Nebuloni, Manuela; Rusconi, Stefano; Santus, Pierachille; et al.
Abstract: Aims: Several reports indicate that diabetes determines an increased mortality risk in patients with coronavirus disease 19 (COVID‐19) and a good glycaemic control appears to be associated with more favourable outcomes. Evidence also supports that COVID‐19 pneumonia only accounts for a part of COVID‐19 related deaths. This disease is indeed characterised by abnormal inflammatory response and vascular dysfunction, leading to the involvement and failure of different systems, including severe acute respiratory distress syndrome, coagulopathy, myocardial damage and renal failure. Inflammation and vascular dysfunction are also well‐known features of hyperglycemia and diabetes, making up the ground for a detrimental synergistic combination that could explain the increased mortality observed in hyperglycaemic patients. Materials and methods: In this work, we conduct a narrative review on this intriguing connection. Together with this, we also present the clinical characteristics, outcomes, laboratory and histopathological findings related to this topic of a cohort of nearly 1000 subjects with COVID‐19 admitted to a third‐level Hospital in Milan. Results: We found an increased mortality in subjects with COVID‐19 and diabetes, together with an altered inflammatory profile. Conclusions: This may support the hypothesis that diabetes and COVID‐19 meet at the crossroads of inflammation and vascular dysfunction. (ClinicalTrials.gov NCT04463849 and NCT04382794).